Pengaruh Keadilan Pajak, Diskriminasi, Dan Religiusitas Terhadap Persepsi Penggelapan Pajak - Salma Salsabila; Garin Pratiwi Solihati (Excellent, 2025)
This study investigates the impact of tax justice, perceived discrimination, and religiosity on individuals’ perceptions of tax evasion. The research focuses on accounting students at Mercu Buana University, observed over a three-year period from 2021 to 2023. The total population consists of 477 students. The sample was selected using an accidental sampling technique, a non-probability method wherein The selection of study participants was determined by their readiness to participate voluntarily. From this process, 112 usable responses were successfully collected. This research utilized firsthand information gathered directly from survey participants through the administration of systematic questionnaire instruments. The analytical approach involved implementing Partial Least Squares Structural Equation Modeling (PLS-SEM) methodology. The research outcomes demonstrate that tax fairness and feelings of discriminatory treatment both show substantial positive correlations with taxpayer evasion attitudes. Conversely, although religious beliefs also exhibit a positive association with evasion perceptions, this relationship lacks statistical significance in the findings.